Examining exposure to adverse childhood experiences and later outcomes of poor physical and mental health among South Carolina adults. (January 2018) - Crouch, Elizabeth; Strompolis, Melissa; Radcliff, Elizabeth; Srivastav, Aditi
Abstract: Recent research on adverse childhood experiences (ACEs) has used factor analysis to categorize ACEs. Further research is needed to determine if these previously identified factors are related to specific health outcomes. Using data obtained from the 2014–2015 South Carolina Behavioral Risk Factor Surveillance System, this study assessed the association between categories (household dysfunction; emotional and physical abuse; sexual abuse) and combinations of categories of ACEs on mental and physical health outcomes in adulthood ( n  = 15, 638). Respondents who had all three categories of abuse were much more likely to report poor health and mental distress. Sexual abuse in childhood increased the odds of reporting poor health and mental distress; some ACEs may have stronger associations to long term health than others. These findings can help lead to effective and targeted prevention or intervention strategies that incorporate the new insight on the combination of ACE categories that are likely to co-occur. Highlights: The underlying factors of the ACE survey are related to long-term mental and physical health outcomes. Respondents with multiple types of abuse are more likely to report poor health and mental distress. Prevention of co-occurring ACE categories can improve long-term health.